TRAINING DRILL FOR ENCHANCING STRENGTH AND BALANCE OF THE ELDERLY WITH APPLIED YOGA ACTIVITIES - Hemara, Chaturong; Kong-u-rai, Umaporn; Rodma, Gosol; Dhanajyaist, Bhumip (Academic Journal of Thailand National Sports University, 2020)
This research was conducted in a research and development method. The purposes of this study were to: 1) develop the training drill for enhancing strength and balance of the elderly with applied yoga activities; and 2) investigate the efficiency of the training drill for enhancing strength and balance of the elderly with applied yoga activities. The samples used in this study were 70 of the elderly in Lampang Province. The stages of this study were as follows: 1) developing the training drill by documentary review such as textbooks and research and finding the quality of the training drill by an assessment method; 2) seeking for the efficiency of the training drill with try-out method and strength and balance assessment in a pre and post experiment design. The data were analyzed in mean, standard deviation and t-test (Independent). The results were found that 1) training drill for enhancing strength and balance of the elderly with applied yoga activities consisted of 3 main components, factor elements, process elements, driven mechanism elements and its quality was found at a good level; 2) the efficiency of the training drill was found that the mean scores of strength and balance in the experimental group were higher than that in the control group at the significant difference level of 0.05.